Transforaminal Endoscopic Discectomy and Foraminoplasty for Treating Central Lumbar Stenosis. Issue 6 (12th November 2019) - Bao, Bei‐xi; Zhou, Jian‐wei; Yu, Pan‐Feng; Chi, Cheng; Qiang, Hua; Yan, Hui
Abstract : Objective: Lumbar spinal stenosis is a medical condition characterized by the narrowing of the spinal canal as a consequence of bone and soft tissue degeneration, including disc herniation, facet and ligamentum flavum hypertrophy, and osteophyte formation. The percutaneous transforaminal endoscopic discectomy (PTED) technique is one of the emerging surgical alternatives for treating central lumbar stenosis. The present study aims to describe the present techniques of PTED and foraminoplasty for central lumbar stenosis, and discuss the feasibility and advantages of this technique. Methods: A total of 55 patients with an average age of 50 years were recruited in this study. They were operated on between August 2017 and June 2018 by a single surgeon for symptomatic lumbar stenosis using the PTED and foraminoplasty technique, along with a detailed description of the present technique. The retrospective analysis of 55 patients operated between August 2017 and June 2018 by a single surgeon for symptomatic lumbar stenosis using the PTED and foraminoplasty techniques, and the detailed description of the present technique were the focus of the present study. For all patients, the PTED and foraminoplasty procedure was performed under local anesthesia in the lateral position on a radiolucent table using C‐arm fluoroscopy. The retrospective analysis evaluated the outcomes of symptoms through follow‐up interviews at six weeks, six months, and one year after surgery. The analyzed parameters included surgery time, intraoperative blood loss, postoperative complications, visual analog scale (VAS) score, Japan Orthopedic Association (JOA) score, and the Oswestry Disability Index (ODI). The modified MacNab criteria were adopted. Results: The average duration of symptoms was 15.6 weeks. The mean operative time was 161 minutes. The mean volume of intraoperative blood loss was 21 mL. The mean follow‐up period was 14.6 months. The average preoperative VAS score for leg pain and low back pain was 6.8 and 5.5, respectively. The preoperative ODI and JOA score was 49.2 and 14.6, respectively. At the final follow‐up, all 55 patients had an average VAS score of 1.1 for leg pain and 0.5 for low back pain. At the same time, the average ODI and JOA score was seven and 24.5, respectively. The statistical analysis showed that the VAS score, ODI value, and JOA score were significantly lower in all time‐points at post‐operation, when compared to those at pre‐operation. For the modified MacNab criteria, the final outcome results were excellent in 39 patients (70.9%), good in nine patients (16.4%), fair in four patients (7.3%), and poor in two patients (3.6%), and the overall success rate was 89.1%. Two patients underwent a second operation during the follow‐up period, and their symptoms were released after the reoperation. Conclusion: PTED and foraminoplasty technique showed promising outcomes in the treatment of central lumbar stenosis in a 1‐year follow‐up period. It suggested that PTED and foraminoplasty might be applied as a safe and effective therapeutic option for patients with lumbar stenosis.